Storyworlds: the little girl and the bear - Riordan, James (Heinemann UK, 2009)
"The Little Girl and the Bear" is a heartwarming children's book that tells the story of a young girl who befriends a bear. In the story, the girl and the bear share an unlikely but beautiful friendship, learning from each other as they explore nature together. Through their adventures, they discover the importance of compassion, kindness, and respecting the natural world. The book highlights the power of empathy and understanding, showing that even the most unexpected friendships can bring joy and valuable lessons.